STRATEGI MANAJEMEN SUMBER DAYA MANUSIA DAN DIGITAL MARKETING UMKM SEBAGAI UPAYA MENINGKATKAN DAYA SAING - Muhammad Chandra Fauzan; Muhammad Bintang Ramadhan; Rifka Agus Pratama (Taksasila Edukasi Insani, 2026)
The rapid advancement of digital technology has intensified business competition and encouraged micro, small, and medium enterprises (MSMEs) to adopt more adaptive strategies. Alongside digital transformation, effective human resource management plays a crucial role in strengthening business competitiveness. This study aims to examine the role of human resource management strategies and digital marketing in enhancing MSME competitiveness through a literature review approach. The study analyzes relevant national journal articles published between 2021 and 2025 that discuss human resource management, digital marketing, and MSME competitiveness. The findings indicate that the integration of human resource development and digital marketing strategies contributes positively to market expansion, operational efficiency, and customer engagement. MSMEs supported by competent human resources and adequate digital capabilities tend to be more responsive to market changes and better positioned to sustain their competitive advantage. This study provides a conceptual contribution by emphasizing the importance of aligning human resource management with digital marketing strategies in the digital era.Keywords: human resource management, digital marketing, MSMEs, business competitiveness